2019
DOI: 10.1080/20013078.2019.1608786
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond size and phosphatidylserine exposure: evidence for a diversity of apoptotic cell‐derived extracellular vesicles in vitro

Abstract: Apoptosis is a form of programmed cell death that occurs throughout life as part of normal development as well as pathologic processes including chronic inflammation and infection. Although the death of a cell is often considered as the only biological outcome of a cell committed to apoptosis, it is becoming increasingly clear that the dying cell can actively communicate with other cells via soluble factors as well as membrane-bound extracellular vesicles (EVs) to regulate processes including cell clearance, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(143 citation statements)
references
References 91 publications
(229 reference statements)
4
131
0
1
Order By: Relevance
“…However, phosphatidylserine is also exposed on apoptotic bodies, which are larger vesicles specifically formed during the late stages of apoptosis [97,98]. Apoptotic bodies can be distinguished from other phosphatidylserine-positive MVs based on positivity for caspases 3 and 7 and their substrates (e.g., ROCK1 and PANX1) [99], while size is unreliable, because apoptotic bodies (~0.1 to~5 µm) overlap in size with other EV subtypes [99]. Here, it should be remarked that phosphatidylserine exposure, although often used as a surrogate marker of apoptosis [100], does not distinguish apoptotic bodies from other MVs [84,99].…”
Section: Microvesicles and Apoptotic Bodiesmentioning
confidence: 99%
“…However, phosphatidylserine is also exposed on apoptotic bodies, which are larger vesicles specifically formed during the late stages of apoptosis [97,98]. Apoptotic bodies can be distinguished from other phosphatidylserine-positive MVs based on positivity for caspases 3 and 7 and their substrates (e.g., ROCK1 and PANX1) [99], while size is unreliable, because apoptotic bodies (~0.1 to~5 µm) overlap in size with other EV subtypes [99]. Here, it should be remarked that phosphatidylserine exposure, although often used as a surrogate marker of apoptosis [100], does not distinguish apoptotic bodies from other MVs [84,99].…”
Section: Microvesicles and Apoptotic Bodiesmentioning
confidence: 99%
“…Phosphatidylserine is also expressed by apoptotic body membranes, and for this reason, the positivity to Annexin V (which is related to the surface exposure of phosphatidylserine) is not a useful method that allows to distinguish apoptotic bodies and microvesicles derived from activated cells. Apoptotic bodies must be identified, instead, for their positivity to the caspase substrates [33].…”
Section: Extracellular Vesicles Subtypesmentioning
confidence: 99%
“…Apoptotic bodies are membrane vesicles of approximately 50-2000 nm in diameter, released during the programmed cell apoptosis processes ( Figure 1) [30,34]. Given that apoptotic cells express phosphatidylserine on their surface [35], the positivity to Annexin V (which binds phosphatidylserine) has been considered a hallmark of apoptotic bodies, even if the enrichment in caspase 3 and 7 has been proposed to be more specific for apoptotic bodies [33]. It has been recently demonstrated that, as with all the other EV subtypes, apoptotic bodies represent an active vehicle of intercellular communication from dying to living cells [14].…”
Section: Extracellular Vesicles Subtypesmentioning
confidence: 99%
“…Finally, the release of distinct ApoBDs from the cell occurs [ 60 ]. As with exosomes and MVs, ApoBDs are enriched in proteins associated with their biogenesis, including caspase 3-cleaved ROCK1, PlexB2 and PANX1 [ 61 , 62 ]. In addition, cytokines, growth factors and nuclear material have also been detected within ApoBDs [ 24 , 47 , 63 ].…”
Section: Ev Diversity In Healthy and Dying Cells—mechanisms Of Biomentioning
confidence: 99%
“…Whether these EVs were generated through energy-dependent mechanisms, such as exosome formation or membrane shedding, or their specific cargo, was not determined. Furthermore, as it has been previously shown the ApoBDs can lyse over time [ 62 ]; the ability of ApoBDs undergoing lysis to subsequently reform into more EVs is also of interest.…”
Section: Inflammatory Evs Generated During Different Modes Of Cellmentioning
confidence: 99%